An overview about oxidation in clinical practice of skin aging - Silas Arandas Monteiro e Silva; Bozena Michniak-Kohn; Gislaine Ricci Leonardi (Sociedade Brasileira de Dermatologia, 2017)
Abstract Free radicals are unstable chemical species, highly reactive, being formed by cellular entities of different tissues. Increased production of these species without proper effective action of endogenous and exogenous antioxidant systems, generates a condition of oxidative stress, potentially provider of skin disorders that extend from functional impairments (skin cancer, dermatitis, chronic and acute inflammatory processes) even aesthetic character, with the destruction of structural proteins and cellular changes with the appearance of stains, marks and lines of expressions and other signs inherent to the intrinsic and extrinsic skin aging process. The antioxidants are chemical substances commonly used in clinical practice for topical application and may contribute in the fight against the radical species responsible for many skin damage. This paper summarized the main evidence of the benefits brought by the topical application of antioxidants in the skin, considering the amplitude of the indicative performance of antioxidant activity by in vitro and ex-vivo tests as well as in vivo tests. It is recognized that a breadth of product performance tests should be explored to truly identify the effectiveness of antioxidant products for an anti-aging effect.